Preparation and evaluation of a green solvent-based molecularly imprinted monolithic column for the recognition of proteins by high-performance liquid chromatography. Issue 21 (25th September 2019) - Ma, Wanwan; An, Yena; Row, Kyung Ho
Abstract : A protein-based molecularly imprinted monolithic column was synthesized based on ionic liquids (ILs) and deep eutectic solvents (DESs) in a stainless steel column (50 mm × 4.6 mm id). Abstract : A protein-based molecularly imprinted monolithic column was synthesized based on ionic liquids (ILs) and deep eutectic solvents (DESs) in a stainless steel column (50 mm × 4.6 mm id). An IL (1-allyl-3-butylimidazolium Br) and acrylamide were used as dual monomers. Another type of IL (1, 2-bis [ N, N ′-vinylimidazolium] ethane bis Br) and N, N ′-methylenebisacrylamide were used as dual cross-linking agents, and the DES (choline chloride : ethylene glycol 1 : 2) was used as a porogen in the preparation of a monolithic polymer. Bovine serum albumin (BSA) and lysozyme (Lyz), which differ greatly in molecular size, isoelectric point, and charge, were selected for imprinting templates to evaluate the recognition property of the green solvent-based MIP monolithic column. Some important factors, such as template–monomer molar ratio, total monomer concentration, and cross-linking density, were investigated systematically. Under optimal conditions, the MIP monolithic column obtained showed higher binding affinity for the templates than its corresponding non-imprinted (NIP) monolithic column.